Analisis Determinasi Volume Ekspor Minyak Kelapa Sawit Sumatera Utara - Monang Hutapea; Pinondang Nainggolan; Pawer Darasa Panjaitan; Darwin Damanik (Universitas Negeri Padang, 2023)
This study aims to determine the effect of exchange rates, land area, international prices and previous international prices as independent variables on the volume of palm oil exports 2003 -2022 as the dependent variable. This study uses the PAM (Partial Adjustment Model) or Nerlove's Model approach, while to analyze the effect of the independent variables on the dependent variable, the analysis tool of the coefficient of determination (Adjusted R2) is used and the partial test uses the t-statistic test and the test together uses the F test. -statistics where all of the above tests use the calculations of the Eviews 12 program. The results show that the exchange rate has a negative and significant effect, land area has a positive and significant effect, international prices have a positive and significant effect, and international prices in the previous period have a positive and significant effect on the volume of oil exports North Sumatran oil palm 2003 – 2022.